2021
DOI: 10.1016/j.virusres.2021.198575
|View full text |Cite
|
Sign up to set email alerts
|

A simple pooling salivary test for SARS-CoV-2 diagnosis: A Columbus’ egg?

Abstract: Saliva is an appropriate specimen for Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) diagnosis. The possibility of pooling samples of saliva, using non-invasive bibula strips for sampling, was explored employing Bovine coronavirus (BCoV) spiked saliva. In laboratory, up to 30 saliva-soaked strips were pooled in a single tube with 2mL of medium. After quick adsorption with the medium and vortexing, the liquid was collected and tested with a quantitative molecular assay to qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…This is guaranteed by the high sensitivity of the rRT-PCR which allows to identify even a single positive sample within a pool containing up to 19 negative samples. By performing the test on the 20 pooled samples, the difference between the median Ct value of test performed on the single positive NS and the median Ct value obtained on the 20 samples-pool was 3.11, 3.7, and 4.11 Ct, for E, RdRp and N gene, respectively, thus confirming that pooling strategy is at least as sensitive as testing individual samples ( Pratelli et al, 2021 ). This datum confirms that, even if the pool contains only one low viral load positive sample, the sensibility of the test is not substantially affected.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…This is guaranteed by the high sensitivity of the rRT-PCR which allows to identify even a single positive sample within a pool containing up to 19 negative samples. By performing the test on the 20 pooled samples, the difference between the median Ct value of test performed on the single positive NS and the median Ct value obtained on the 20 samples-pool was 3.11, 3.7, and 4.11 Ct, for E, RdRp and N gene, respectively, thus confirming that pooling strategy is at least as sensitive as testing individual samples ( Pratelli et al, 2021 ). This datum confirms that, even if the pool contains only one low viral load positive sample, the sensibility of the test is not substantially affected.…”
Section: Resultsmentioning
confidence: 80%
“…Anyhow, NPS collection is time-consuming, uncomfortable, invasive, can generate stress (chiefly for children), requires trained health care personnel and is associated with a no negligible risk of viral transmission ( Azzi et al, 2021 ). These difficulties were addressed and innovative approaches were proposed for simpler and less invasive sampling and for accelerating the screening of groups of people and large populations ( Czumbel et al, 2020 ; Pratelli et al, 2021 ). From the very first months of pandemic onset, growing interest was addressed to the use of self-collected sampling as a suitable first-line screening test for SARS-CoV-2 infection ( Böger et al, 2020 ; Mohammadi et al, 2020 ; Tsang et al, 2021 ), reducing the risk for healthcare workers involved in sampling, and increasing the number of analyses where supplies of personal protection equipment (PPE) are lacking or difficult to find.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we observed greater sensitivity values in pooling NS samples than pooling SL samples. This may be due to a lower viral load of SL samples (higher Cts) as compared to NS or NP samples reported in prior studies [ [16] , [17] , [18] ]. Nevertheless, the specificity of both approaches was very high.…”
Section: Discussionmentioning
confidence: 84%